Gastrointestinal duplication cysts in children - Saraç, Mehmet; Bakal, Ünal; Tartar, Tugay; Kazez, Ahmet (Logos Medical Publishing, 2018)
Aim: In this research, we aimed to present the characteristics of gastrointestinal duplication cysts (GIDC), surgical treatments applied, and operative results because of their rarity. Material and Methods: Age, gender, presence of prenatal diagnosis (if any), symptoms and physical examination, radiological and surgical findings and clinical results of the patients were recorded. Results: A total of 11 GIDC patients were treated within 12 years. Average age of the patients was 42 months (2 days-15 years) and their M/F ratio was 6/5. The patients had ileal (n=6), duodenal (n=3), and cecal (n=1) duplications, and duplications involving ileum, appendix, caecum and entire column were detected in 1 patient. Six patients were treated with intestinal resection and anastomosis (n=6), cystectomy (n=3), partial cystectomy and mucosectomy (n=1) and cystotomy and mucosectomy (n=1) (Wreen's procedure). In one case, resection anastomosis in the terminal ileum and cysto-colonic anastomosis from the sigmoid colon level were performed and opening of the distal part of the cyst into the colonic lumen was ensured. Conclusion: GIDC's may necessitate different surgical approaches depending on their location. 2017 © Logos Medical Publishing. All Rights Reserved.
Çocuklarda gastrointestinal duplikasyon kistleri
Keywords: Children; Duplication cyst; Gastrointestinal